Kern - Beaulieu, Derek (punctum books, 2023)
Proposed as a collection of imaginary logos for the corporate sponsors of Borges's Library of Babel, Kern balances on a precipice between the visual and nonsensical, offering poems just out of meaning's reach. Using dry-transfer lettering, Derek Beaulieu made these concrete pieces by hand, building the images gesturally in response to shapes and patterns in the letters themselves. This is poetry closer to architecture and design than confession, in which letters are released from their usual semantic duties as they slide into unexpected affinities and new patterns. Kern highlights the gaps inside what we see and what we know, filling the familiar with the singular and the just seen with the faintly remembered.